O discurso midiático na legitimação do punitivismo - Pedroso, Suellen Elissa Zaparoli (2021)
The main objective of this project is to discuss about how the media subject affects and interferes in criminalization, and consequently create stereotyped enemies, reinforcing the classic functions of punishment, which are prevention and resocialization. The culture of fear, that faces the idea of risk, and the anxious willing of the population for safety, usually creates a suitable background for this scenario. Denying its complexity and partiality as well as basing itself on the pretension of audience, the media frequently works based in ideological concepts, obscuring the latent functions of the penalty. Therefore, this peculiar aforementioned method uses different strategies, such as thematic selectivity, colloquial language, absence of sources, selective dualism building enemies and heroes, exposure of the ideal victim and vengeful revenge speech. In daily practice, the penal system is unable to prevent crimes or re-socialize the convict. This, in turn, is used as a symbol of punishment in pursuit of collective satisfaction for security. The idea of revenge, retribution and resocialization spread by the media creates the idea of humanity improvement that is presumed able to justify the perpetuation of punitiveness. Zaffaroni's Agnostic Theory lays on this power insofar as it reveals its latent functions, and is an alternative to limit and reduce the exercise of irrational and illegitimate violence. The instrumentalization of punishment, which uses the individual in search of the common well-being, is characteristic of utilitarianism and leads to an authoritarian penal system, based on irrational impulses, which only serves to cause oppression and pain. Human dignity is the foundation of the legal system, being innate and radiating over all other rights. Therefore, it limits the punitive power of the State and guarantees minimum rights, even if the protected person is a defendant or convict. The media is the main mechanism to spread information and produce opinion in the society. Thus, it is necessary that the media has its narrative about crime restructured by ethical and plural principles, in order to give a voice to all those involved, respecting essential rights and also being the guarantor of a Democratic State limited by legality and dignity